Shopping Center-Based Design Transit Oriented Development (TOD) (Case Study: Pulo Brayan Kec Market. Medan Baru) - Audina Dzulhijwandari; Rahmadhani Fitri; Bhakti Alamsyah (Sean Institute, 2021)
One of the activities that humans do every day is shopping and this activity is a favorite habit for today's society. The existence of a shopping place in a city has always been the most interesting and memorable place because it is a place that is often v isited by city residents. In Pulo Brayan where there are people with various activities and professions, one of which is as a seller in the market that requires Mixed-Use Building in the design of shopping centers with transit oriented development (TOD) system facilities in order to integrate a walkable, safe, and comfortable environment so as to optimize commercial facilities by increasing the use of public mass transit in transit in the city. As well as having considerations from various aspects as a whole that will determine the attractiveness of a shopping center to visitors.